Effect of COVID-19 on presentations of decompensated liver disease in Scotland. Issue 1 (6th January 2022) - Manship, Thomas; Brennan, Paul N; Campbell, Iona; Campbell, Stewart; Clouston, Thomas; Dillon, John F; Forrest, Ewan; Fraser, Andrew; Goh, Tee Lin; Johnston, Michael; Khan, Muhammad I; Livie, Victoria; et al.
Abstract : Background and aims: SARS-CoV-2 and consequent pandemic has presented unique challenges. Beyond the direct COVID-related mortality in those with liver disease, we sought to determine the effect of lockdown on people with liver disease in Scotland. The effect of lockdown on those with alcohol-related disease is of interest; and whether there were associated implications for a change in alcohol intake and consequent presentations with decompensated disease. Methods: We performed a retrospective analysis of patients admitted to seven Scottish hospitals with a history of liver disease between 1 April and 30 April 2020 and compared across the same time in 2017, 2018 and 2019. We also repeated an intermediate assessment based on a single centre to examine for delayed effects between 1 April and 31 July 2020. Results: We found that results and outcomes for patients admitted in 2020 were similar to those in previous years in terms of morbidity, mortality, and length of stay. In the Scotland-wide cohort: admission MELD (Model for End-stage Liver Disease) (16 (12–22) vs 15 (12–19); p=0.141), inpatient mortality ((10.9% vs 8.6%); p=0.499) and length of stay (8 days (4–15) vs 7 days (4–13); p=0.140). In the Edinburgh cohort: admission MELD (17 (12–23) vs 17 (13–21); p=0.805), inpatient mortality ((13.7% vs 10.1%; p=0.373) and length of stay (7 days (4–14) vs 7 days (3.5–14); p=0.525)). Conclusion: This assessment of immediate and medium-term lockdown impacts on those with chronic liver disease suggested a minimal effect on the presentation of decompensated liver disease to secondary care.